MO237: Rituximab in Treatment of Minimal Change Disease and Primary Focal Segmental Glomerulosclerosis in Adults-Single Center Experience. (3rd May 2022) - Zagorec, Nikola; Horvatic, Ivica; Kasumović, Dino; Toric, Luka; Šenjug, Petar; Galešić Ljubanović, Danica; Galesic, Kresimir
Abstract: BACKGROUND AND AIMS: Rituximab (RTX) showed some efficacy in treatment of minimal change disease (MCD) and primary focal segmental glomerulosclerosis (pFSGS) [1 ]. The results of its off-label use and as steroid-sparing agent were especially promising in steroid-dependent, frequently relapsing or steroid-resistant forms of MCD and pFSGS in adults [2 ]. METHOD: All patients treated with RTX in Department of Nephrology and Dialysis, University Hospital Dubrava, Zagreb, were retrospectively reviewed. Complete remission (CR), steroid-resistant nephrotic syndrome (SRNS), steroid-dependent nephrotic syndrome (SDNS), multidrug-resistant SRNS (MDR-SRNS) and calcineurin inhibitor (CNI)-resistant SRNS were defined according to KDIGO 2021 [3 ]. RESULTS: Of 82 patients treated with RTX, 11 patients had biopsy proven MCD and pFSGS. Table 1 summarizes relevant demographic, clinical and treatment data. RTX was applied in five patients with SDNS, four patients with MDR-SRNS, one patient with CNI-resistant SRNS and one patient with active hepatitis C and newly onset MCD as a first line therapy. Median follow-up after initial diagnosis and RTX application was 122.9 (range 30–219) and 20 (range 3–117) months, respectively. All patients were initially treated with steroids, and RTX was the drug most commonly applied after treatment with CNI and cyclophosphamide (CYC). Median proteinuria at the time of RTX application was 10 g/day (range 2.5–16.7), 10 patients had preserved kidney function and only 1 patient with collapsing FSGS (case 11) had severe acute kidney injury. Mean cumulative dose of RTX for induction was 1700 mg and short course of steroids was used concomitantly in 10 cases (except case 5). CR was achieved in seven cases (six cases of MCD and one case of MDR-FSGS). Three of seven patients with CR to RTX experienced relapse of disease. Time to relapse was 6, 15 and 40 months in case 5, 3 and 11, respectively. Repeated RTX application led to CR in all three cases. CR persisted in five patients even after the steroids cessation. There were no serious adverse effects of RTX administration in our cohort. CONCLUSION: RTX showed respectable efficacy in our cohort of adults with SDNS-MCD and in case of MDR collapsing FSGS. Although statistical comparison was not performed because of small number of patients, it seems that RTX is more effective in group of SDNS than MDR-SRNS. In our cohort, patients with relapse of RTX-sensitive disease responded to repeated application. Role of RTX in treatment of MCD and pFSGS should be evaluated in randomized clinical trials.